The Calcination Temperature Effect on Crystal Structure of LiNi1/3Mn1/3Co1/3O2 Cathode Material for Lithium-Ion Batteries - Rahayu, Sri; Saudi, Aghni Ulma; Tasomara, Riesma; Gumelar, Muhammad Dikdik; Utami, Wahyu Tri; Hapsari, Ade Utami; Raharjo, Jarot; Rifai, Abdulloh; Khaerudini, Deni Shidqi; Husin, Saddam; Saputra, Dita Adi; Yuliani, Hanif; Andrameda, Yurian Ariandi; Taqwatomo, Galih; Arjasa, Oka Pradipta; Damisih, Damisih; Hardiansyah, Andri; Pravitasari, Retna Deca; Agustanhakri, Agustanhakri; Budiman, Abdul Hamid (Journal of Batteries for Renewable Energy and Electric Vehicles, 2023)
The lithium-ion battery has gained popularity among other secondary batteries for portable electronic devices and electric vehicle applications, especially the LiNi1/3Co1/3Mn1/3O2 or NMC111, considering its well-balanced configuration resulting in stable and safe electrochemical performance. NMC111 has been successfully prepared using a coprecipitation process at calcination temperatures from 800 to 950°C. The physical characteristics were investigated using X-Ray Diffraction (XRD), Scanning Electron Microscopy-Energy Dispersive Spectroscopy (SEM-EDS), and Particle Size Analysis (PSA). The XRD patterns showed the rhombohedral single phase for all calcination temperatures. Meanwhile, higher calcination temperatures offer higher degree of crystallinity, lower intensity ratio and more undesirable cation mixing. The particles with a uniform rectangle or pyramid shape are observed at the calcination temperature range from 800 to 900°C. However, bigger submicron particles with a rectangle or pyramid shape are detected at a higher temperature (950°C). The SEM-EDS mapping shows the homogeneity composition for all variation calcination temperatures. PSA analysis showed that calcination temperature at 800 and 850°C gives the particle less than 400 nm suggesting a potential material for a cathode of lithium-ion batteries.